2016
DOI: 10.1177/1077699016654680
|View full text |Cite
|
Sign up to set email alerts
|

Do Not Stand Corrected

Abstract: Abstract:The accelerating news cycle means there is a risk that errors become more common, but digital media also allow for correcting errors continuously and being transparent about this. In this study, we investigate Swedish citizens' attitudes toward errors and corrections. The results demonstrate that citizens have strong expectations that news media publish correct information and they have little tolerance for errors. People's background and media use do not affect attitudes toward errors and corrections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(26 citation statements)
references
References 59 publications
1
23
0
2
Order By: Relevance
“…But as Aikin et al’s (2015) experiment showed, exposure to corrective direct-to-consumer drug advertisements helped reduce the belief in the claims of violative misleading medicine ads on asthma patients, yet exposure to both corrective ads and violative ads did not improve accuracy rating on the drug’s side effects and risks. There are also potential backlash effects using fact checking and corrections when people were told they were wrong and lowered their trust in the media with corrections or other accusations of liberal bias in fact-checking services (Karlsson, Clerwall, & Nord, 2017; Tucker, Theocharis, Roberts, & Barberá, 2017). More unconventional methods to prevent spreading fake news such as borrowing the story-telling techniques and testimonials used successfully by antivaccine activists have been proposed to help distribute correct information to the people (Shelby & Ernst, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…But as Aikin et al’s (2015) experiment showed, exposure to corrective direct-to-consumer drug advertisements helped reduce the belief in the claims of violative misleading medicine ads on asthma patients, yet exposure to both corrective ads and violative ads did not improve accuracy rating on the drug’s side effects and risks. There are also potential backlash effects using fact checking and corrections when people were told they were wrong and lowered their trust in the media with corrections or other accusations of liberal bias in fact-checking services (Karlsson, Clerwall, & Nord, 2017; Tucker, Theocharis, Roberts, & Barberá, 2017). More unconventional methods to prevent spreading fake news such as borrowing the story-telling techniques and testimonials used successfully by antivaccine activists have been proposed to help distribute correct information to the people (Shelby & Ernst, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This style of reporting has grown tremendously in the United States and overseas over the last decade, and especially since 2010 (Amazeen, 2013; Fridkin, Kenney, & Wintersieck, 2015; Graves, Nyhan, & Reifler, 2015; Kessler, 2014; Stencel, 2016). It is separate from traditional, internal fact-checking by news organizations seeking to weed out errors before publishing a story or to correct past mistakes, although all these reflect journalism’s defining professional preoccupation with factual accuracy (Chalaby, 1996; Karlsson, Clerwall, & Nord, 2016). Contemporary fact-checking has precursors in the muckraking journalism of the early 20th century, which exposed deception in both the political and business worlds—for instance, challenging false claims of patent-medicine producers.…”
Section: Fact-checking Motivated Reasoning and Truth Scalesmentioning
confidence: 99%
“…When a media outlet exposed a Republican as making a false claim, Republicans saw the outlet as biased toward Democrats, and vice-versa. At the same time, however, media outlets suffer when they make mistakes, particularly among consumers with low levels of media trust (Karlsson et al, 2016); this suggests that the public holds them to high standards, and may welcome journalists taking a more active role in fact-checking. Indeed, fact-checking as a whole tends to benefit media outlets: Those that regularly engage in fact-checking are evaluated more favorably than those that do not (Pingree et al, 2014; Thorson, 2013).…”
Section: Truth Scales’ Effect On Reader Attitudesmentioning
confidence: 99%
“…The BAI questionnaire assesses the level of respondents' anxiety using a scale based on the respondents' answers to the existing 20 questions. There are four scales in BAI, namely low (0-7), medium (8)(9)(10)(11)(12)(13)(14)(15), high (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and severe . In this experiment, the BAI questionnaire was filled out by respondents after reading the three news articles provided in the context of real news content, and this can provoke impulses and respondents' memories to trigger anxiety.…”
Section: Anxiety Measurementmentioning
confidence: 99%
“…Social media news is low-cost, easy to access, and enables rapid dissemination of online news for more significant consumption, although with the negative impact of the wide spread of "fake news" [12]. On the other hand, readers strongly expect news websites to publish correct information and have little tolerance for error [13]. However, at present, most news and information sites on the internet have a few negative biases; one of them is digital misinformation.…”
Section: Introductionmentioning
confidence: 99%